Anatomic and Physiologic Heterogeneity of Subgroup-A Auditory Sensory Neurons in Fruit Flies - Ishikawa, Yuki; Okamoto, Natsuki; Nakamura, Mizuki; Kim, Hyunsoo; Kamikouchi, Azusa (Frontiers in Neural Circuits, 2017)
The antennal ear of the fruit fly detects acoustic signals in intraspecific communication, such as the courtship song and agonistic sounds. Among the five subgroups of mechanosensory neurons in the fly ear, subgroup-A neurons respond maximally to vibrations over a wide frequency range between 100 and 1,200 Hz. The functional organization of the neural circuit comprised of subgroup-A neurons, however, remains largely unknown. In the present study, we used 11 GAL4 strains that selectively label subgroup-A neurons and explored the diversity of subgroup-A neurons by combining single-cell anatomic analysis and Ca2+ imaging. Our findings indicate that the subgroup-A neurons that project into various combinations of subareas in the brain are more anatomically diverse than previously described. Subgroup-A neurons were also physiologically diverse, and some types were tuned to a narrow frequency range, suggesting that the response of subgroup-A neurons to sounds of a wide frequency range is due to the existence of several types of subgroup-A neurons. Further, we found that an auditory behavioral response to the courtship song of flies was attenuated when most subgroup-A neurons were silenced. Together, these findings characterize the heterogeneous functional organization of subgroup-A neurons, which might facilitate species-specific acoustic signal detection.